A study on cations and color removal from thin sugar juice by modified sugar beet pulp - Arslanoğlu, Hasan; Tümen, Fikret (My University, 2012)
This article describes the use of citric acid modified sugar beet pulp as new ion-exchanger sorbent for the removal of metal cations and colorants from thin juice. The results of batch adsorption runs concerning the effects of contact time, material dosage, temperature and pH drop were presented and discussed. Experimental data on the removal of metal cations showed that the sorption process was rapid and reached equilibrium in 60 min. Modified material in acidic form caused to a significant pH drop in thin juice, which could result with sucrose inversion. Uptake of metal cations increased with temperature whereas that of color decreased. Neutralised type modified product gave more satisfying results. After six successive contacts, 49.7%, 37.5% and 43.7% removals for Ca-Mg, K and color, respectively, were obtained by using neutralised form of modified sugar beet pulp.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Sugar beet pulp; Modification; Cation removal; Color removal